Brønsted Acid‐Mediated Annulation of α‐Oxo Ketene Dithioacetals with Pyrroles: Efficient Synthesis of Structurally Diverse Cyclopenta[b]pyrroles. Issue 26 (25th May 2015) - Yang, Xiaoge; Wu, Kaikai; Wu, Ping; Chen, Jiping; Sun, Chenglin; Yu, Zhengkun
Abstract Brønsted acid‐mediated annulation of internal olefins α‐oxo ketene dithioacetals to pyrroles was efficiently achieved to afford cyclopenta[b]pyrroles. A pair of Brønsted acids with acid strengths, that is, trifluoroacetic acid, and para‐toluenesulfonic acid hydrate, were applied to promote the annulation reactions. The resultant products were readily oxidized to sulfones by meta‐chloroperoxybenzoic acid. Subsequent treatment with 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene gave desulfurized terminal olefins or [2+2] cycloaddition products from the desulfurized olefin intermediates. The present protocol provides facile access to structurally diverse cyclopenta[b]pyrrole derivatives under mild conditions.